Low host specificity of herbivorous insects in a tropical forest - Novotny, Vojtech; Basset, Yves; Miller, Scott E; Weiblen, George D; Bremer, Birgitta; Cizek, Lukas; Drozd, Pavel (Nature, 2002)
Two decades of research have not established whether tropical insect herbivores are dominated by specialists or generalists. This impedes our understanding of species coexistence in diverse rainforest communities. Host specificity and species richness of tropical insects are also key parameters in mapping global patterns of biodiversity. Here we analyse data for over 900 herbivorous species feeding on 51 plant species in New Guinea and show that most herbivorous species feed on several closely related plant species. Because species-rich genera are dominant in tropical floras, monophagous herbivores are probably rare in tropical forests. Furthermore, even between phylogenetically distant hosts, herbivore communities typically shared a third of their species. These results do not support the classical view that the coexistence of herbivorous species in the tropics is a consequence of finely divided plant resources; non-equilibrium models of tropical diversity should instead be considered. Low host specificity of tropical herbivores reduces global estimates of arthropod diversity from 31 million (ref. 1) to 4 6 million species. This finding agrees with estimates based on taxonomic collections, reconciling an order of magnitude discrepancy between extrapolations of global diversity based on ecological samples of tropical communities with those based on sampling regional faunas.
Keywords: Plant Leaves; stravovací zvyklosti; Trees; hmyz; druhová specificita; Phylogeny; Molecular Sequence Data; molekulární sekvence - údaje; stromy; Host-Parasite Interactions; New Guinea; zvířata; listy rostlin; Nová Guinea; Insecta; tropické klima; fylogeneze; Species Specificity; Tropical Climate; Animals; Feeding Behavior; interakce hostitele a parazita